How Much Does the Variety of Scenery and the Different Percentages of Audience Occupancy Affect the Indoor Acoustics at the National Theater of Zagreb? - Lamberto Tronchin; Antonella Bevilacqua (Applied Sciences, 2022)
The performance of opera and the post-pandemic slow recovery of the public, who have been hesitant to return to frequent attendance of cultural venues, has inspired the authors to analyze the acoustic behavior of the National Theater of Zagreb, by reflecting five specific scenarios. Starting from acoustic measurements undertaken inside the National Theater of Zagreb without any scenery in place, this research study compares the main acoustic parameters simulated with the scenery of Tosca in three different acts. A numerical model was realized by reproducing the geometry and the architectural features of this historic performance arts space. Before the simulations, the absorption coefficients applied to the digital entities were calibrated with the values gathered from the recorded impulse responses. After the calibration process, the acoustic simulations were also carried out with the presence of an audience at two percentages of occupancy.